Diagnostic and prognostic significance of extent of subepithelial electron dense deposits in membranous glomerulonephritis. (4th May 2021) - Kipgen, David; Geddes, Colin
ABSTRACT: There are limited data concerning the range and diagnostic significance of the extent of subepithelial electron dense deposits (SEEDD) in membranous glomerulonephritis (MGN). We described the range, and assessed the diagnostic and prognostic significance of extent of SEEDD, particularly in patients with sparse SEEDD, where diagnostic difficulty can arise. Adult renal biopsies with a confident or suspected histological diagnosis of MGN between 2013 and 2020 were included. Patients were classified based on extent of SEEDD as having either global MGN (GMGN, >75% SEEDD), segmental MGN (SMGN, 25%–75% SEEDD), or sparse-SEEDD (<25% SEEDD). Clinical and other features were compared. One hundred and eleven (74%) patients had GMGN; 23 (15%) had SMGN; and 16 (11%) had sparse-SEEDD. Patients with sparse-SEEDD had a significantly shorter duration of nephrotic syndrome prior to biopsy. 53% of patients with GMGN and 14% with SMGN had serum anti-phospholipase A2 receptor (PLA2r) antibodies. Patients with sparse-SEEDD did not have anti-PLA2r antibodies. Urine protein:creatinine ratio was significantly lower in sparse-SEEDD patients after 3, 6, 9, and 12 months. The proportion of sparse-SEEDD patients in complete remission from nephrotic range proteinuria at 6 and 12 months was significantly higher than that of GMGN patients. Analysis of a subgroup suggested sparse-SEEDD patients responded more rapidly to steroid containing immunosuppression than GMGN patients. There is a wide range of extent of SEEDD in patients with MGN. Sparse-SEEDD appears distinct from SMGN and GMGN and may be either an early form of MGN, or an epiphenomenon associated with another primary disease process, particularly minimal change disease.